Uncommon Ehrlichia canis infection associated with morulae in neutrophils from naturally infected dogs in Brazil - Aguiar, Daniel Moura (2020)
Ehrlichia and Anaplasma species are the most common tick-borne disease (TBD) pathogens in dogs worldwide. Ehrlichia canis, the aetiological agent of the Canine Monocytic Ehrlichiosis (CME), is known to replicate within the cytoplasm of mononuclear cells into clusters of organisms called morulae. However, detection of morulae in neutrophils is commonly observed in dogs infected by Ehrlichia ewingii or Anaplasma phagocytophilum. We report uncommon clinical cases of canine ehrlichiosis presenting morulae compatible with E. ewingii and A. phagocytophilum in dogs from two distinct regions of Brazil. Eight dogs were admitted to two veterinary teaching hospitals from Brazil, showing clinical or haematological signs suggestive of TBD. Blood or peritoneal fluid was withdrawn for haematological and cytologic analysis. All samples were evaluated by PCR assays for Ehrlichia and Anaplasma using genus-specific primers for dsb, 16S rRNA and groEL genes, followed by sequencing. Samples were also evaluated by nested PCR assays for the 16S rRNA gene of E. ewingii and groEL gene of A. phagocytophilum and Anaplasma platys. Seven dogs revealed thrombocytopenia, six dogs had monocytosis and five presented lymphopenia and anaemia. All dogs showed morulae structures compatible with Ehrlichia spp. in neutrophils and were PCR-positive for the dsb and 16S rRNA gene fragments of Ehrlichia, with sequences showing 100% identity with multiple E. canis sequences deposited in the GenBank™. Sequencing of 16S rRNA and groEL gene fragments from one PCR-positive dog showed 100% identity with A. platys. Overall, our data suggest that in endemic regions for E. canis, that is Brazil, the presence of morulae in neutrophils may indicate infection by this bacterium. Herein, morulae were also found in neutrophils present in the peritoneal fluid of a dog. Also, this is the first report of E. canis and Hepatozoon canis co-infection in neutrophils from naturally infected dogs confirmed by DNA sequencing.